2009
DOI: 10.1128/aem.00202-09
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Noroviruses in Ready-To-Eat Foods by Using Carbohydrate-Coated Magnetic Beads

Abstract: This study used histo-blood group antigen-conjugated beads to detect norovirus (NoV) in contaminated strawberries, green onions, lettuce, and deli ham. In addition, multiple strains of NoV from genogroups I and II were recovered. This provides an effective protocol for food testing in the investigation of suspected NoV outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Cationic bead capture is an attractive concept as it may allow the detection of a wide range of viruses without pre-clearing samples. Recently, porcine mucin or synthetic histo-blood group antigens (HBGAs) have been coupled to magnetic beads for the concentration of NoV from food and environmental samples (Cannon and Vinje 2008;Morton et al 2009;Tian et al 2008). HBGAs have been proposed as the norovirus receptor and they have been proven to bind multiple strains of norovirus in vitro (Morton et al 2009;Tan and Jiang 2007).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cationic bead capture is an attractive concept as it may allow the detection of a wide range of viruses without pre-clearing samples. Recently, porcine mucin or synthetic histo-blood group antigens (HBGAs) have been coupled to magnetic beads for the concentration of NoV from food and environmental samples (Cannon and Vinje 2008;Morton et al 2009;Tian et al 2008). HBGAs have been proposed as the norovirus receptor and they have been proven to bind multiple strains of norovirus in vitro (Morton et al 2009;Tan and Jiang 2007).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Recently, porcine mucin or synthetic histo-blood group antigens (HBGAs) have been coupled to magnetic beads for the concentration of NoV from food and environmental samples (Cannon and Vinje 2008;Morton et al 2009;Tian et al 2008). HBGAs have been proposed as the norovirus receptor and they have been proven to bind multiple strains of norovirus in vitro (Morton et al 2009;Tan and Jiang 2007). While magnetic beads are not a universal solution, they have the advantage of being easily separated from a number of food types, which eliminates upstream processing steps and saves time.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Elution, using basic buffer or chemical treatment are often used before concentration step based on filtration or precipitation (Table 5). (Morton et al, 2009) …”
Section: Methods Of Detection For Viruses In Foodsmentioning
confidence: 99%
“…Histo-blood group antigens (HBGAs) have been characterized recently as receptors for HuNoV, and receptor-based capture assays have been applied to concentrate HuNoV from spiked food samples and spiked concentrated environmental water samples (2,21,33). Two-log-unit increases in the sensitivity of HuNoV detection in spiked food samples by a similar method have been reported (33).…”
mentioning
confidence: 98%
“…Several studies demonstrated that a HBGA receptor-based capture method could be used to concentrate HuNoV from food samples (21,33) and facilitate the removal of PCR inhibitors from concentrated water samples (2). Recently, Huhti et al (8) reported using an HBGA-binding assay together with electron microscropy (EM) to confirm morphological integrity, antigenicity, and functionality of HuNoV GII-4 viral like particles.…”
mentioning
confidence: 99%